2007
DOI: 10.1152/jn.00051.2007
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Regulation of Proopiomelanocortin Neurons Can Occur Distal to the Arcuate Nucleus

Abstract: Energy homeostasis is controlled to a large extent by various signals that are integrated in the hypothalamus. It is generally considered that neurons in each of the hypothalamic nuclei are regulated by afferent projections that terminate within the cell body region of the nucleus. However, here it is shown that hypothalamic proopiomelanocortin (POMC) neurons receive synaptic inputs onto distal dendrites that reside outside of the cell body region in the arcuate nucleus. Previous studies using whole cell recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…In randomly selected pSTAT3 IR (POMC) dendritic structures in brains of Lepr db/db ; Pomc-cre;HA-Leprb flox mice we did not find direct evidence of spines by EM. This is consistent with earlier reports by Hentges et al [59] and Liu et al [16] showing a low number of dendritic spines on POMC neurons. By CLSM, which allows rapid analysis of much larger fields and longer fiber distances, we did however observe pSTAT3 IR within rare spine-like structures on POMC dendrites (Figure S9).…”
Section: Resultssupporting
confidence: 94%
“…In randomly selected pSTAT3 IR (POMC) dendritic structures in brains of Lepr db/db ; Pomc-cre;HA-Leprb flox mice we did not find direct evidence of spines by EM. This is consistent with earlier reports by Hentges et al [59] and Liu et al [16] showing a low number of dendritic spines on POMC neurons. By CLSM, which allows rapid analysis of much larger fields and longer fiber distances, we did however observe pSTAT3 IR within rare spine-like structures on POMC dendrites (Figure S9).…”
Section: Resultssupporting
confidence: 94%
“…We found that without TTX, low doses of ACEA (200 nM) induced depolarization of POMC neurons (Fig. 1d 2 ), as reported earlier 12 , while high doses of ACEA (1 µM) resulted in hyperpolarization of POMC cells (Fig. 1d 3 ).…”
Section: Cb1r Drives Activation Of Pomc Neuronssupporting
confidence: 88%
“…However, in these mice GABAergic but not glutamatergic synaptic input is tonically inhibited by endogenous cannabinoids acting on the distal dendrites of POMC neurons, as evidenced by the ability of CB 1 receptor antagonists to increase mIPSC frequency (Hentges et. al., 2005;Hentges, 2007;Sinnayah et. al., 2008).…”
Section: Discussionmentioning
confidence: 99%